Wayside School gets a little stranger [large type] - Sachar, Louis, 1954- (Sachar, Louis, 1954- Wayside School series., 2020)
Unusual things continue to happen in the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.